Response of Enchytraeus crypticus worms to high metal levels in tropical soils polluted by copper smelting - Konecný, Ladislav
Tropical soils from the vicinity of the Mufulira copper smelter (Zambian Copperbelt) were found to contain high levels of metals, particularly in the upper parts of soil horizons. Metal concentrations varied within the ranges: 37-8980mg Cu/kg, 3-46mg Co/kg, <2.5-42mg Pb/kg, and 16-83mg Zn/kg. The EDTA extractions indicated that a considerable percentage of the metals were bound in the "labile" fractions of the soil (up to 55% of total Cu concentration, 36% Co, 41% Pb, 30% Zn). The mineralogical investigation of the heavy mineral fraction of the most contaminated soil showed that the Cu is mainly present as Cu-(Fe) sulphides (chalcocite, chalcopyrite), metallic Cu, complex Cu-(Fe) oxides, and Cu-bearing sulphates. To determine the toxicity of these soils, we adopted a standardized OECD reproduction test using Enchytraeus crypticus. The number of reproduced enchytraeids correlated negatively with total Cu and Co concentrations (r=-0.97 and -0.94 at p<0.001, respectively), and EDTA-extractable Cu (r=-0.89, p<0.001); whereas no effects of the soil properties (pH, CEC, Corg) were observed. No reproduction was possible in soils with Cu levels >5000mg/kg. Median effect concentration (EC50) was calculated for total Cu concentration, and corresponded to 351mg/kg.